دلالات الالفاظ المشتركة في القرآن وأثرها في تعدد التفسيرات - عبد فاطمة علي (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This Praise be to Allah, Lord of the worlds, and may the blessings and peace of Allah be upon the trustworthy Prophet, our Master Muhammad, and all his family. This study addresses the phenomenon of polysemous (ambiguous) words in the Qur’anic text, focusing on their linguistic nature and their impact on the diversity of interpretations. It is well known that the fields of Arabic linguistics are closely linked to Qur’anic studies, as the Noble Qur’an was revealed in clear Arabic, and the relationship between it and the Arabic language is deeply intertwined and inseparable. One of the linguistic topics relevant to the interpretation of the Book of Allah is that of polysemous words—so what is meant by polysemy? What is the stance toward it regarding the interpretation of the Noble Qur’an? And what are some examples from the Qur’an? The study adopts a semantic-analytical approach, which involves identifying words that carry two or more meanings and analyzing them according to the Qur’anic context in which they appear. Such words pose a challenge in determining the intended meaning in the contexts they occur in, thus opening the door wide for research, investigation, and analysis of these words.